Influencing Companies’ Green Governance Through the System of Legal Liability for Environmental Infractions in China and Brazil: Lighting the Way Toward BRICS Cooperation - D. Wei; A. P. Rafael (BRICS Law Journal, 2023)
As a platform of cooperation among its member states, questions of whether or how the BRICS alliance can inﬂuence and shape the global governance system and improve their internal governance systems have often been raised. In the process of exploring the role that the law can play in this context, comparative studies on the laws of the BRICS member states, particularly in the deﬁned areas of cooperation, are an important perspective to be addressed in order to be able to contribute to the improvement of their internal governance systems. However, much work remains to be done on this perspective. This article partially ﬁlls this gap by conducting a comparative study related to one of the BRICS areas of cooperation – sustainable development – between two of its members: China and Brazil. Speciﬁcally, it compares how both states, as stakeholders, use the legal regime of liability for environmental infractions to inﬂuence the green governance of companies. The article, therefore, uses comparative legal methodology, using as its objects of research relevant legal provisions on legal liability for environmental infractions gathered from the legal systems of China and Brazil. The adoption of strict civil liability, liability for environmental damages per se and the extension of criminal liability to legal persons are among the similarities found. As for the diﬀerences, it ﬁnds that, as a principle, Chinese law shields directors and senior oﬃcers from liability toward third parties, while Brazilian law fully extends such liability to these entities; additionally, in the Chinese legal system, the burden of disproving causality between the harm and the activity that caused it falls upon the actor, while the Brazilian legal system adopts a double-standard approach for collective suits and individual suits; and ﬁnally, the Chinese law imposes a legal obligation to adopt what, in eﬀect, is close to a corporate environmental management system, while the Brazilian legal system lacks a similar mandate.